Eurasian Vector of Foreign Policy of the Republic of Korea: the Factor of Central Asia - M. A. Bulanakova (Евразийская интеграция: экономика, право, политика, 2021)
The article studies the role of cooperation between the Republic of Korea and Central Asian countries in the context of a continental strategy for Korea’s New Northern policy. The authors consider the main political discourses of the continental policy of the Republic of Korea, such as the problem of resolving the “Korean issue”, the problem of balancing interests in the East Asian region, and the problem of diversifying traditional partnerships. Korea’s foreign policy is interpreted within the framework of the “middle power” concept. An important part of the study is the analysis of cooperation between RoK and Central Asia both on a multilateral and bilateral basis. It is obvious that uneven two-way interaction of Korea with the Central Asian countries, encourages the RoK to implement specific projects relevant to the partners, at the same time, the RoK uses multilateral cooperation, to predict the cooperation prospects in the most relevant areas of cooperation — health, environment, digital policy. Attracting data of the current situation in the region and the world, the author notes important changes in the foreign policy of RoK, first of all, the ODA strengthening as an important tool for strengthening Korea in a specific region, as an important resource for solving problems of the pandemic COVID-19 impact. As the research result, the author comes to the conclusion that the implementation of the Eurasian vector in Korea’s foreign policy is a natural and necessary condition for the further development of Korea as a regional and global player. Cooperation with Central Asia is a priority resource for developing RoK’s international influence and an important component of the new Northern policy.